Macroeconomic effects of tariffs shocks: The role of the effective lower bound and the labour market - Pascal Jacquinot; Matija Lozej; Massimiliano Pisani (European Central Bank (ECB), 2020)
We simulate a version of the EAGLE, a New Keynesian multi-country model of the world economy, to assess the macroeconomic effects of US tariffs imposed on one country member of the euro area (EA), and the rest of the world (RW). The model is augmented with an endogenous effective lower bound (ELB) on the monetary policy rate of the EA and country-specific labour markets with search-and-matching frictions. Our main results are as follows. First, tariffs produce recessionary effects in each country. Second, if the ELB holds, then the tariff has recessionary effects on the whole EA, even if it is imposed on one EA country and the RW. Third, if the ELB holds and the real wage is exible in the EA country subject to the tariff, or if there are segmented labour markets with directed search within each country, then the recessionary effects on the whole EA are amplified in the short run. Fourth, if the elasticity of substitution among tradables is low, then the tariff has recessionary effects on the whole EA also when the ELB does not hold.
Keywords: F16; F41; F42; F45; F47; 330; DSGE models; protectionism; unemployment; monetary policy